Shapping Business Proffesionals - The, Star (Star Special, 2014)
I am enjoying my DBA studies at AeU, which provides a wealth of knowledge and stimulating discussions. The programmer inculcates unique approach and allows me to combine my expertise in academic research and working knowledge to come up with innovative solutions that are applicable at my workplace. - Christopher Chew, a Doctor of Business Administration student at AeU